Validity of longitudinal sections for determining the apical constriction. (7th July 2016) - Schell, S.; Judenhofer, M. S.; Mannheim, J. G.; Hülber‐J, M.; Löst, C.; Pichler, B. J.; ElAyouti, A.
Abstract: Aim: To validate the use of longitudinal sections against cross sections using micro‐CT for disclosing the topography and location of the apical constriction. Methodology: Seventy extracted human teeth with 117 completely developed roots were micro‐CT scanned and reconstructed at a voxel size of 27 μm. The 3DSlicer program was used to navigate the longitudinal sections parallel to the long axis of the canal and also to rotate and tilt the views. Each root canal was evaluated in both mesio‐distal and bucco‐lingual planes. Constriction topographies were identified as described in the literature. In each canal, the number of different topographies detected was recorded. Further, serial cross‐sectional analysis of the apical portion of the canal was performed. Reconstructed plots of canal areas were assessed to locate the constriction and determine its form. A descriptive analysis of both longitudinal and cross section methods was conducted. In each canal, the frequency of constriction forms was calculated in the mesio‐distal or bucco‐lingual aspects and the 99% confidence interval was computed. Results: When both aspects of the longitudinal sections were pooled, all root canals had two or more topographies and consequently different locations of the apical constriction. In contrast, cross‐sectional analysis constantly yielded one constriction form per canal. Conclusion: Compared to cross‐sectional analysis, longitudinal sections of the root canal conveyed inconsistent results regarding the topography and the location of the apical constriction.